α-Halogenated Curcumins - Phuong-Truc T. Pham; Mamoun M. Bader (Crystals)
α- or 4-Substituted curcumin analogues are scarce. We describe herein the syntheses and crystal structures of the first α-halogenated curcumin derivatives: (1E,6E)-1,7-bis (4-hydroxy-3-methoxyphenyl)-4-bromo-5-hydroxy-1,3,6-heptatriene-3-one or (4-bromocurcumin) (1) and (1E,6E)-1,7-bis (4-hydroxy-3-methoxyphenyl)-4-chloro-5-hydroxy-1,3,6-heptatriene-3-one or (4-chlorocurcumin) (2). We note that the key step in the successful synthesis of the bromo-analog is the use of slightly acidic media to favor the diketo form of curcumin prior to carrying out the reaction. Both newly prepared compounds assume the keto–enol form in the solid state and crystallize in the monoclinic space group P21/c with four molecules in the unit cell each with slightly different dimensions. Inter- and intra- molecular hydrogen bonds were observed in the two structures. Most significant observed features were the inter-molecular O…O distances of 2.842 and 2.840 Å and intra-molecular O…O distances of 2.460 and 2.451 Å for bromo-or (1) and chloro- or (2) derivatives, respectively. No close halogen…halogen contacts were observed in either of the two structures. Both molecules are nearly planar with torsion angles of 0.54 and 1.16 °C between the planes of two terminal phenyl groups for (1) and (2), respectively. π-Stacks were observed in both structures with interplanar distances of 3.367 and 3.454 Å for the bromo- and chloro- compounds, respectively. Hirshfeld surface analysis confirms quantitively a picture of the inter- and intra-molecular interactions in both compounds compared with polymorph I (the most common form) of curcumin. UV–Vis absorption spectra are shifted to higher wavelengths with lmax of 475 and 477 nm for compounds 1 and 2, respectively, compared with 442 nm in dichloromethane solutions. The newly synthesized molecules will open the door for numerous possible synthetic modifications of the α-carbon to prepare valuable analogues of curcumin with more favorable solubility profiles.